The complex metabolism of trimethylamine in humans: endogenous and exogenous sources. (29th April 2016) - Chhibber-Goel, Jyoti; Gaur, Anamika; Singhal, Varsha; Parakh, Neeraj; Bhargava, Balram; Sharma, Amit
Abstract : Trimethylamine (TMA) is a tertiary amine with a characteristic fishy odour. It is synthesised from dietary constituents, including choline, L-carnitine, betaine and lecithin by the action of microbial enzymes during both healthy and diseased conditions in humans. Trimethylaminuria (TMAU) is a disease typified by its association with the characteristic fishy odour because of decreased TMA metabolism and excessive TMA excretion. Besides TMAU, a number of other diseases are associated with abnormal levels of TMA, including renal disorders, cancer, obesity, diabetes, cardiovascular diseases and neuropsychiatric disorders. Aside from its role in pathobiology, TMA is a precursor of trimethylamine-N-oxide that has been associated with an increased risk of athero-thrombogenesis. Additionally, TMA is a major air pollutant originating from vehicular exhaust, food waste and animal husbandry industry. The adverse effects of TMA need to be monitored given its ubiquitous presence in air and easy absorption through human skin. In this review, we highlight multifaceted attributes of TMA with an emphasis on its physiological, pathological and environmental impacts. We propose a clinical surveillance of human TMA levels that can fully assess its role as a potential marker of microbial dysbiosis-based diseases.